Implementasi Alat Pencacah Daun Bambu Kering sebagai Media Tanam dengan Arduino Uno - Marcelita, Faldiena; Novianty, Inna; Sholihah, Walidatush (MULTINETICS, 2022)
Dried bamboo leaves were chosen as a planting media for strengthen nutrients and improve soil drainage. Before being processed into fertilizer, the dried bamboo leaves will be chopped first. The problem that exists is that the chopping of dried bamboo leaves is still manually using a knife and scissors so it is quite time consuming and less effective. Making a dry bamboo leaf chopper with Arduino uno to chop dry bamboo leaves with a limit switch sensor so that it can rotate and stop the chopper blade automatically. The process of making this tool uses a method, namely, design to design hardware, software, and casing design, manufacture, namely the implementation of the design, and testing to carry out the testing phase of the tool so that the tool runs according to its purpose. The manufacture of this tool consists of hardware components which include Arduino uno, limit switch, DC motor, BTS7960 motor driver, step down LM2596, and power supply as well as software using Arduino IDE. The result of making a dry bamboo leaf chopper with Arduino uno is that it can chop dry bamboo leaves according to the purpose. This tool can chop up to 50 grams of dry bamboo leaves. Suggestions in making this tool are development by adding automation when the container is full and the tool automatically runs as well as increasing the duration of counting on the tool.